Roles and Responsibilities of the Principal: Building a Positive Learning Environment Based on the Concept of Tri Hita Karana at SD Negeri 4 Babahan - Aresta, Gede Oditya; Widayanti, Gusti Ayu Neta Putri; Vionita, Agustina Putu; Sitepu, Cica Marsela Br; Rendra, Gede Chandra Sekha; Pramana, I Gede Agus Julio; Juliani, Luh Dinda; Werang, Basilius Redan (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to examine the roles and responsibilities of the principal in building a positive learning environment at SD Negeri 4 Babahan. A conducive learning environment plays an important role in improving student motivation and achievement. This research used a qualitative approach with a case study design. The research subjects involved students, teachers and the principal. Data were collected through interviews, observations, and document analysis, then analyzed using thematic analysis techniques. The results showed that principals play a key role in building a supportive learning atmosphere, including through developing school policies, improving the quality of teaching and learning processes, and strengthening relationships between schools, parents and communities. In addition, the principal's responsibilities include managing human resources and physical facilities, as well as implementing innovative programs that involve the active involvement of students.